Engagement risk, auditor choice and audit fee in the Malaysian audit market - Mohamad Naimi, Mohamad Nor (2015)
High risk of auditor litigation and audit market competitiveness motivate audit firms to place greater emphasis on the role of engagement risk in determining client-auditor relationship and audit cost (Johnstone, 2000; Johnstone & Bedard, 2004). Based on this development, this study examines the market structure and the impact of engagement risk on auditor choice and audit pricing in a low litigation risk setting. Drawing from the agency theory and its related hypotheses, the study anticipates that audit risk, auditor business risk and client business risk are significantly associated with auditor choice and audit fee. The samples of study consist of Malaysian public listed companies from 2008 to 2010. The descriptive analysis of 2,854 companies demonstrates that the Malaysian audit market can be described as a tight oligopoly. In determining the influence of risk on auditor choice and audit fee, some exclusion criteria were established. Using panel data analysis on 2,451 companies, it is found that engagement risk significantly influences auditor choice and audit fee. In particular, auditor business risk is more important than the other risks in auditor choice and it is positively associated with the choice of quality auditor whereas, audit risk elements are more dominant than the other risk factors in explaining audit fee. Auditors will charge higher audit fees for clients with higher audit risks. The engagement risk affects auditor choice and audit fee differently because of the different risk management practices by audit firms in establishing their client portfolio. Avoidance of small and risky clients among large audit firms would increase companies’ difficulty to access the capital market and delay growth. This study contributes to the auditing literature by addressing the audit firm’s risk management strategy in Malaysia, which is rarely investigated. The study also provides an insight into the regulator on factors that should be considered in enhancing the quality of an audit firm